Tuck everlasting - Babbitt, Natalie (Farrar, Straus, Giroux, 1975)
The Tuck family is confronted with an agonizing situation when they discover that a ten-year-old girl and a malicious stranger now share their secret about a spring whose water prevents one from ever growing any older.